2013
DOI: 10.1021/ma402008b
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Water Content and Proton Conductivity through Copolymer Morphology

Abstract: To investigate relationships between morphology and proton conductivity in ionic copolymer membranes, we have studied two series of fluorous copolymers bearing polystyrene grafts sulfonated from 0 to 100%. Small-angle X-ray and neutron scattering experiments reveal a disordered, partially phase-separated system consisting of fluorous domains in a partially sulfonated polystyrene matrix with aggregation of ion-rich domains within the matrix. The size of the fluorous domains depends on graft density, and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
4
23
0
Order By: Relevance
“…Figure B shows that the proton conductivity increases linearly with the water content. These results are consistent with other studies that show that different morphological changes are related to proton conductivity and its relationship with water content . Figure C shows the relationship between the correlation length of hydrated membranes and the water content for SIBS SO 3 H ‐ PHFBMA membranes.…”
Section: Resultssupporting
confidence: 92%
“…Figure B shows that the proton conductivity increases linearly with the water content. These results are consistent with other studies that show that different morphological changes are related to proton conductivity and its relationship with water content . Figure C shows the relationship between the correlation length of hydrated membranes and the water content for SIBS SO 3 H ‐ PHFBMA membranes.…”
Section: Resultssupporting
confidence: 92%
“…Due to the chemical dissimilarity, the side‐chains and the matrix are generally not miscible, and segregate spontaneously. This phase separation defines the morphology of the hydrophilic and hydrophobic phases which directly influences the water uptake, the percolation threshold, the tortuosity of the aqueous phase, and the ion conductivity . The ability to tailor the lengths of the incompatible polymer strands is an asset for the optimization of PEMs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was demonstrated that phase separation between fluorinated polymer and PS phase is limited because of the competition with the sulfonated acid groups aggregation mechanism. The similarities in water uptake and conductivity values for membranes of radically different morphology were also pointed out, particularly when volume-based quantities from references [45] and [53] are compared. To summarize, the present SANS study points out that the control of water uptake through the macromolecular structure is a key feature in designing efficient materials.…”
Section: Bcp Ionomer Membranesmentioning
confidence: 90%
“…100-0, 70-30, 40-60 and 0-100. [53] The respective SLDs are -0.56, 1.52, 2.91, and 6.37 × 10 10 cm -2 . The fluorinated polymer SLD was estimated at 2.87 × 10 10 cm -2 and the polystyrene one 1.41 × 10 10 cm -2 ; consequently, contrast matching can be expected.…”
Section: Bcp Ionomer Membranesmentioning
confidence: 95%